CryoEM‐Guided Development of Antibiotics for Drug‐Resistant Bacteria. (12th February 2019) - Belousoff, Matthew J.; Venugopal, Hari; Wright, Alexander; Seoner, Samuel; Stuart, Isabella; Stubenrauch, Chris; Bamert, Rebecca S.; Lupton, David W.; Lithgow, Trevor
Abstract: While the ribosome is a common target for antibiotics, challenges with crystallography can impede the development of new bioactives using structure‐based drug design approaches. In this study we exploit common structural features present in linezolid‐resistant forms of both methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococcus (VRE) to redesign the antibiotic. Enabled by rapid and facile cryoEM structures, this process has identified ( S )‐2, 2‐dichloro‐ N ‐((3‐(3‐fluoro‐4‐morpholinophenyl)‐2‐oxooxazolidin‐5‐yl)methyl)acetamide (LZD‐5 ) and ( S )‐2‐chloro‐ N ‐((3‐(3‐fluoro‐4‐morpholinophenyl)‐2‐oxooxazolidin‐5‐yl)methyl) acetamide (LZD‐6 ), which inhibit the ribosomal function and growth of linezolid‐resistant MRSA and VRE. The strategy discussed highlights the potential for cryoEM to facilitate the development of novel bioactive materials. Abstract : The bacterial ribosome is a common target for antibiotics. However, it is a difficult drug target for structural study by conventional X‐ray crystallography. We report the use of single‐particle cryo‐electron microscopy to aid in the structure‐based drug design of new antibiotics based on the oxazolidinone, linezolid. We use this technique to show by a rational design approach that it is possible to synthesise new antibiotics with antibacterial activity against linezolid‐resistant forms of both methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant Enterococcus .